2013
DOI: 10.1517/14656566.2013.810208
|View full text |Cite
|
Sign up to set email alerts
|

Psoriatic arthritis: current therapy and future directions

Abstract: Presently, it is agreed upon that use of tumor necrosis factor inhibitors (TNFi) has greatly changed our ability to manage varying aspects of disease in PsA. However, there remain many unanswered questions in which research in PsA is mirroring RA work, these include: i) the need for outcome measures that are more specific to PsA, ii) the concept of early and treat to target, iii) the role of highly sensitive imaging, and iv) efficacy of combination therapy and further targets in those unable to tolerate or fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The patterns of PsA involvement are symmetric or asymmetric arthritis, distal interphalangeal predominant arthritis, spondylitis and arthritis mutilans . Psoriasis (PsO) usually antedates arthritis in 80% of patients with PsA . A recent systematic review underscores that the results of comorbidity studies in PsA is inconsistent related to the heterogeneity of the control groups .…”
Section: Introductionmentioning
confidence: 99%
“…The patterns of PsA involvement are symmetric or asymmetric arthritis, distal interphalangeal predominant arthritis, spondylitis and arthritis mutilans . Psoriasis (PsO) usually antedates arthritis in 80% of patients with PsA . A recent systematic review underscores that the results of comorbidity studies in PsA is inconsistent related to the heterogeneity of the control groups .…”
Section: Introductionmentioning
confidence: 99%
“… 105 These new therapeutic concepts for PsA include a high efficacy of combination therapy in those unable to tolerate or who have failed TNF inhibitor treatment. 106 …”
Section: Combination Therapy Using Biological Therapeuticsmentioning
confidence: 99%
“…105 These new therapeutic concepts for PsA include a high efficacy of combination therapy in those unable to tolerate or who have failed TNF inhibitor treatment. 106 Relapsing ocular involvement is a major manifestations of BD and occurs in 60-80% of patients, resulting in retinal vasculitis, neuropathy or panuveitis. 107 TNF inhibitors are effective and safe in these patients, especially regarding its corticosteroid-and immunosuppressive drug-sparing effects.…”
Section: Combination Therapy Using Biological Therapeuticsmentioning
confidence: 99%
“…Etanercept, another anti-TNF agent, has proven efficacy in the treatment of axial SpA100 , but not in IBD. Concerning peripheral arthritis, anti-TNF agents have demonstrated efficacy in psoriatic arthritis (adalimumab, certolizumab, etanercept)101 and adalimumab also showed promising results in two placebo-controlled trials in patients with peripheral SpA102,103 . Furthermore, the CARE study, a large European open-label trial, showed resolution of EIMs exceeding 50% in CD patients treated with adalimumab, including peripheral arthritis and r-axSpA 104 .6.5 VedolizumabVedolizumab is a gut-selective α4β7 integrin antagonist, modulating gut lymphocyte trafficking.…”
mentioning
confidence: 99%